Endoscopic Septoplasty without Nasal Packing: An Experience in a Tertiary Hospital - Basnet, Meenakshi; Rajkumar, Bedajit; Ghimire, Bibek; Shrestha, Akriti (Journal of Nobel Medical College, 2019)
Background: Deviated nasal septum (DNS) is easily caused by trauma and septal surgeries have evolved from forceful fractures to endoscopic surgery being the leading trend now. Endoscopic surgery has lots of advantage over the conventional headlight method in alleviating symptoms and reducing complications. Endoscopic septoplasty without the nasal packing significantly shorten the surgery time and hospital stay thus reducing the financial burden. Hence this prospective study done in Nobel Hospital and Teaching Center was an Endeavour to see the indications, technique and outcome of the new surgical procedure. Materials and Methods: Sixty-five patients irrespective of sex in the age group of 18-60 years were enrolled in the study from December 2017 to December 2018. All symptomatic DNS confirmed by 00 and 300 rigid endoscope were enrolled. Informed consent from patients and ethical clearance was taken. Results: The maximum patients were in the age group of 18-30 years. The commonest symptoms of the patient was nasal obstruction in 51(78.46%), followed by post-nasal drip in 20(30.76%), hyposmia in 17(26.15%), headache in 15(23.07%) and epitasis in 10(15.38%). According to Mladina classification, the commonest deviated septum was type V in 29(45%), followed by type VI in12(18%), type II and IV in 7(11%) each, type VII in 6(9%) and least being type III in 4(6%) patients. There were no patients with Mladina type I DNS in this study. The improvement in symptoms were 90% in nasal obstruction, 88% in hyposmia, 85% in post nasal drip, 90% inepistaxis and 100% in headache. The complications were haemorrhage in 1(1.5%), synechia2(3.07%), mucosal tear 5(7.69%), haematoma 1(1.5%) and persistant DNS 5(7.69%). The average hospital stay was 48 hours. Conclusion: Endoscopic septoplasty without post-operative packing is very convenient to the patient. Endoscopic septoplasty with trans- septal suture is safe, cost effective and a better alternative.